2014
DOI: 10.1016/j.joca.2014.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Examining sex differences in knee pain: the Multicenter Osteoarthritis Study

Abstract: Objective To determine whether women experience greater knee pain severity than men at equivalent levels of radiographic knee osteoarthritis (OA). Design and Methods A cross-sectional analysis of 2712 individuals (60% women) without knee replacement or a recent steroid injection. Sex differences in pain severity at each KL grade were assessed by knee using VAS scale and WOMAC with and without adjustment for age, analgesic use, BMI, clinic site, comorbid conditions, depression score, education, race, and wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 47 publications
4
80
1
4
Order By: Relevance
“…In persons recruited from the community and clinic with symptomatic knee OA by ACR criteria, different quantitative sensory testing measures were associated with clinical pain in African-Americans and non-Hispanic Caucasians; reduced pain inhibition was important in all groups (71). Women in the Multicenter Osteoarthritis Study reported greater knee pain than men regardless of KL grade; differences decreased with adjustment for widespread pain (72). Higher BMI was associated with greater knee pain accounting for OA severity in persons with or at high risk for knee OA in the Osteoarthritis Initiative (73).…”
Section: Resultsmentioning
confidence: 99%
“…In persons recruited from the community and clinic with symptomatic knee OA by ACR criteria, different quantitative sensory testing measures were associated with clinical pain in African-Americans and non-Hispanic Caucasians; reduced pain inhibition was important in all groups (71). Women in the Multicenter Osteoarthritis Study reported greater knee pain than men regardless of KL grade; differences decreased with adjustment for widespread pain (72). Higher BMI was associated with greater knee pain accounting for OA severity in persons with or at high risk for knee OA in the Osteoarthritis Initiative (73).…”
Section: Resultsmentioning
confidence: 99%
“…Wise et al [54] did not report data on patellofemoral compartment in their study. However, using MOST data, Glass et al [22] recently reported that women have a greater prevalence of patellofemoral OA than men. Furthermore, in knees with patellofemoral OA, women reported greater severity of pain for all KL grades than men.…”
Section: Discussionmentioning
confidence: 99%
“…Neurobiological mechanisms likely contribute to chronic pain in knee OA. It is now well‐established that central and peripheral sensitization are present in knee OA . Peripheral sensitization is defined as the facilitated response of nociceptive neurons located at the site of tissue injury or disease; it is limited to these nociceptors and will resolve as tissues heal and inflammation recedes.…”
mentioning
confidence: 99%